Factors Affecting The Level Of Occupational Stress Among First Line Healthcare Workers Saudi Arabia Hospitals During Covid-19 Pandemic (Journal of Namibian Studies : History Politics Culture, 2022)
Background: the rapid increase in number of covid-19 patients has led to an elevated demand of nursing care services, which may cause physiological issues and concerns among the first line Healthcare Workers. While there are speculations of increased cases of occupational stress among the first line Healthcare Workers, little has been done to verify the rate among Healthcare Workers in Saudi Arabia Hospitals.Purpose: this study was conducted to determine the factors affecting occupational stress among first line Healthcare Workers in Saudi Arabia Hospitals during covid-19 pandemic.Methods: this study applied the cross-sectional correlational design of the quantitative methodology. Data was collected using the occupational stress scale from a randomly sampled 250 first line Healthcare Workers working in Saudi Arabia Hospitals. The collected data was analyzed using Chi-square and descriptive statistics of SPSS.Results: 82.8% of the Healthcare Workers had high level of stress, 17.2% had moderate stress and none had low level of stress. The level of occupational stress is affected by four demographic characteristics, including Healthcare Workers’ age (p=.000; r=.713), level of education (p=.000; r=.655), whether the Healthcare Workers stayed alone or with others (p=.000; r=.507) and marital status (p=.014; r=.624). Six work-related factors were also noted to affect the level of occupational stress, including nature of working conditions (p=.000; r=.597), access to PPEs (p=.000; r=.594), nature of relationship with the other co-workers (p=.000; r=.594), hours of working (p=.000; r=.542), years of experience (p=.002; r=.734) and department of work (p=.040; r=.756).Conclusion: there is a high level of occupational stress among the first line Healthcare Workers. Therefore, there is a need for the healthcare systems to devise measures to address the propagating factors around stress among these Healthcare Workers.